Monetary Policy Regime Shifts and Inflation Persistence - Davig, Troy; Doh, Taeyoung (The Review of Economics and Statistics, 2014)
Using Bayesian methods, we estimate a Markov-switching New Keynesian (MSNK) model that allows shifts in the monetary policy reaction coefficients and shock volatilities with U.S. data. We find that a more aggressive monetary policy regime was in place after the Volcker disinflation and before 1970 than during the Great Inflation of the 1970s. Our estimates also indicate that a low-volatility regime has been in place during most of the sample period after 1984. We connect the timing of the different regimes to a measure of inflation persistence.